Large language models in thyroid diseases: Opportunities and challenges - Yiwen Zhang; Pengfei Li; Lili Xu; Xuejuan Zhang; Hongwei Ji; Yangang Wang (EngMedicine)
The increasing prevalence of thyroid diseases, coupled with their significant social, psychological, and economic burdens renders them a major health challenge. Within the realm of thyroid diseases, numerous challenges persist, including notable knowledge gaps between patients and physicians, uneven distribution of medical resources, and limitations of existing diagnostic tools. The rapid development of large language models holds promise for addressing these problems. However, alongside these prospects lie challenges encompassing limited recency and specialization, privacy and ethical concerns, and the lack of a general evaluation paradigm for dynamically updated large language models. Here, we provide a balanced discussion of the opportunities and challenges associated with using large language models for thyroid diseases.